Decoding the “Pain-to-Door” interval using psychological, medical, and demographic factors: A multi-center study - Hamidreza Roohafza; Feridoun Noohi; Sara Bagherieh; Marjan Mansourian; Media Babahajiani; Hamidreza Marateb; Mohammadjavad Alemzadeh, Ansari; Aboozar Fakhr Mousavi; Mohammad Mehdi Peighambari; Masoumeh Sadeghi (PLoS ONE, 2025)
Background Reducing the amount of time between the onset of symptoms and presentation to a healthcare facility, namely the “pain-to-door” interval, is of utmost importance in patients with myocardial infarction. In the present study, we aimed to shed light on the psychological, medical, and demographic factors that are associated with this vital time, and the details of this association. Methods We used the baseline data of 1685 participants from a 3-year, multi-centric, cohort study. The pain to door time was estimated as the interval between symptoms’ onset and arrival at the hospital. Patients were asked to fill out valid and reliable questionnaires regarding sociodemographic factors, depression, health anxiety, type D personality, sense of coherence, coping strategies, and quality of life. Data was then analyzed to attain the p-value and hazard ratios (HR) of different variables. Results In the multivariate analysis, being male (HR: 0.81, 95% CI: 0.68–0.98) and a history of angina (0.82, 0.69–0.96) were associated with shorter pain-to-door durations. A history of diabetes mellitus also made the cut marginally (p-value: 0.059). On the contrary, health anxiety (1.27, 1.09–1.49), history of depression (1.57, 1.21–2.05), high socioeconomic status (1.25, 1.03–1.51) and sense of coherence (1.34, 1.14–1.57) scores were associated with longer pain-to-door durations. Conclusion Our findings demonstrate that personal, social, and economical characteristics play a pivotal role in determining patients’ pain-to-door time duration. Screening high-risk individuals in terms of the factors that tend to increase the pain-to-door time alongside educating people and healthcare providers on the importance of this interval and its contributing factors must be a priority considering the devastating burden of CVDs.